The Effect of Health Education Through Interactive Educational Videos on Public Knowledge About Handling Post-Flood Diarrhea in the Tilango Health Center Working Area - Fatmawati Nggai; Ita Sulistiani Basir; Ibrahim Suleman (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Floods are one of the disasters that often occur and have an impact on increasing health problems, one of which is diarrhea. Post-flood diarrhea is generally caused by poor sanitation and limited access to clean water. In Indonesia, floods are the most common disasters with 1,166 incidents in 2023 that have an impact on 4.2 million people. In Gorontalo Province, floods occur almost every year which impact tens of thousands of people. Post-flood conditions increase the risk of environment-based diseases, especially diarrhea. This study aims to determine the influence of health education through interactive educational videos on public knowledge about handling diarrhea after flooding in the working area of the Tilango Health Center. The research uses a quantitative method with a pre-experimental design of the one-group pretest-posttest type. The population of 163 people with a sample of 62 respondents used the purposive sampling technique. The research instruments are in the form of knowledge questionnaires and educational video media. Data analysis used the Wilcoxon test. The results of the study showed that there was a significant influence of health education through interactive educational videos on increasing public knowledge with a p-value = 0.000 (? < 0.05). The conclusion of this study is that interactive educational videos are effective in increasing public knowledge about handling diarrhea after floods and can be a sustainable digital media-based health promotion strategy.